TELAAH POLEMIK PEMBATASAN SOSIAL BERSKALA BESAR DITINJAU DARI PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Ari Amalia, Riska; Oktava, M. Saoki (Fakultas Hukum Universitas Nahdlatul Wathan Mataram, 2020)
This study aims to determine and understand the rules regarding Large-Scale Social Restrictions (PSBB), namely whether Government Regulation Number 21 of 2020 concerning Large-Scale Social Limits in the Context of Handling Corona Virus Disease 2019 (Covid 19) delegated by Law Number 6 In 2018, Health Quarantine fulfills formal and material requirements, and whether including PSBB sanctions in governor regulations is justified in statutory regulations. This research is a normative legal research with a statutory approach, conceptual approach, and case approach. The conclusion is that Government Regulation No. 21 of 2020 concerning PSBB in the Framework of Accelerating Handling of Corona Virus Disease 2019 (Covid 19) does not meet formal and material requirements. And that the governor's regulation which contains sanctions is a material defect.